2012
DOI: 10.2345/0899-8205-46.6.478
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Hospital Noise: A Review of Medical Device Alarm Management

Abstract: Increasing noise in hospital environments, especially in intensive care units (ICUs) and operating rooms (ORs), has created a formidable challenge for both patients and hospital staff. A major contributing factor for the increasing noise levels in these environments is the number of false alarms generated by medical devices. This study focuses on discovering best practices for reducing the number of false clinical alarms in order to increase patient safety and provide a quiet environment for both work and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 44 publications
0
43
0
Order By: Relevance
“…A high number of false alarms is often observed and they contribute to desensitization, lack of reliability, and lack of response from professional caregivers (Cvach (3) , citing Lawless). Studies support the idea that the increase in the number of alarms reduces "faith" of healthcare professionals in alarms, at the same time it increases the noise level in the hospital environment (15) . The study by Gazarian (14) showed that practices of nurses regarding the management of alarms is an area with significant weaknesses.…”
Section: Increase In Noise Caused By the Raise In The Number Of Alarmsmentioning
confidence: 67%
See 3 more Smart Citations
“…A high number of false alarms is often observed and they contribute to desensitization, lack of reliability, and lack of response from professional caregivers (Cvach (3) , citing Lawless). Studies support the idea that the increase in the number of alarms reduces "faith" of healthcare professionals in alarms, at the same time it increases the noise level in the hospital environment (15) . The study by Gazarian (14) showed that practices of nurses regarding the management of alarms is an area with significant weaknesses.…”
Section: Increase In Noise Caused By the Raise In The Number Of Alarmsmentioning
confidence: 67%
“…Reducing hospital noise: a review of medical device alarm management (15) 2012 USA Systematic literature review 27 articles…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Therefore, quality improvement initiatives to individualize alarm thresholds and minimize false alarms are crucial to optimize the balance between patient safety and a healing ICU environment, while simultaneously decreasing nurses' stress. [34][35][36][37] Similarly, the institution of nighttime quiet hours both in patient rooms and general areas can change culture and minimize sound due to staff conversations, enabling adherence to recommendations 2 of the World Health Organization that sound levels should be no more than 30 dB at night. However, current evidence suggests that most PICUs internationally do not have either noise or light optimization protocols in place for sleep promotion.…”
Section: Appendix Continuedmentioning
confidence: 99%